Recommendations for the Establishment and Operation of Human Milk Banks in Europe: A Consensus Statement From the European Milk Bank Association (EMBA) - Weaver, Gillian; Bertino, Enrico; Gebauer, Corinna; Grovslien, Anne; Mileusnic-Milenovic, Radmila; Arslanoglu, Sertac; Barnett, Debbie; Boquien, Clair-Yves; Buffin, Rachel; Gaya, Antoni; Moro, Guido E.; Wesolowska, Aleksandra; et al. (Frontiers in Pediatrics, 2019)
OBJECTIVES: To develop recommendations from the European Milk Bank Association (EMBA) for the establishment and operation of human milk banks (HMB) in Europe. METHOD: A working group comprising members of the EMBA was convened in 2015 to develop Europe-wide recommendations for milk banks. Each member had experience of guideline development and/or milk banking operations. An initial survey was agreed using collated published global recommendations. A total of 108 potential recommendations were included in the survey; responders noted which were included in their national guidelines. The responses were collated, compared and discussed and the group determined where there was consensus and where substantial or minor differences were identified. Where there was consensus or robust published evidence on which to base recommendations these were included. When there was no consensus and no clear evidence base, a statement of explanation based on collective expert opinion was agreed. RESULTS: Published, internationally available guidelines with recommendations for human milk banks from France, Italy, and the UK, together with guidelines from Austria, Denmark, Germany, Norway, Slovakia, Spain, Sweden and Switzerland were included as source materials. These covered: General recommendations; Donor recruitment and screening; Expression, handling and storage of donor human milk (DHM); Pooling of DHM; Milk screening; Milk treatment (pasteurisation); Delivery of DHM to recipients. CONCLUSIONS: Evidence based recommendations and consensus statements from the EMBA will now be published on the EMBA website to assist in the safe establishment and operation of HMBs throughout Europe. These have also been used to inform the chapter on human milk to be included in the 2019 edition of the Guide to the quality and safety of tissues and cells for human application, published by the European Directorate for the Quality of Medicines & HealthCare (EDQM)